Antipruritic Effect of Topical Acetaminophen Gel in Histaminergic and Non-histaminergic Itch Provocation: A Double-blind, Vehicle-controlled Pilot Study - Leigh A. Nattkemper; Kaining Zhi; Kaeli E. Romero; Serena M. Shah; Teresa Ju; Kayla Fourzali; Rachel Shireen Golpanian; Flor MacQuhae; Yiong Huak Chan; David B. Lebo; Gil Yosipovitch (Medical Journals Sweden, 2022)
There is a need for new topical antipruritics that are effective on many types of itch. This study examined the antipruritic efficacy of a new formulation of topical acetaminophen. In vitro skin permeability studies showed that 2.5% and 5% formulations are able to rapidly deliver an adequate amount of the drug into the skin. In a double-blind, vehicle-controlled, randomized study in 17 healthy volunteers, 1%, 2.5% and 5% acetaminophen gels and a vehicle gel were applied to the skin prior to histaminergic and non-histaminergic itch induction and assessment of thermal pain thresholds. The 2.5% and 5% gel formulations significantly reduced the itch intensity time course and the area under the curve for both histamine and cowhage itch. No effect was noted on heat pain thresholds and no adverse effects were observed. These results suggest that topical acetaminophen would be a safe and effective over-the-counter medication for itch.